2016
DOI: 10.1088/0256-307x/33/4/047601
|View full text |Cite
|
Sign up to set email alerts
|

Broad-Band FMR Linewidth of Co 2 MnSi Thin Films with Low Damping Factor: The Role of Two-Magnon Scattering

Abstract: The low Gilbert damping factor, which is usually measured by ferromagnetic resonance, is crucial in spintronic applications. Two-magnon scattering occurs when the orthogonality of the ferromagnetic resonance mode and other degenerate spin wave modes was broken by magnetic anisotropy, voids, second phase, surface defects, etc., which is important in analysis of ferromagnetic resonance linewidth. Direct fitting to linewidth with Gilbert damping is advisable only when the measured linewidth is a linear function o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In recent years it has been realized that TMS linewidths are pervasive for the conventional in-plane geometry of thin film FMR measurements, requiring either the perpendicularto-plane FMR geometry [13] (for which TMS processes are suppressed) or sufficiently broadband measurements [14] to extract the bare Gilbert α. For instance, recent FMR linewidth studies on Heusler compounds have reported distinct TMS linewidths [15,16], which challenged simple inference of the Gilbert α.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years it has been realized that TMS linewidths are pervasive for the conventional in-plane geometry of thin film FMR measurements, requiring either the perpendicularto-plane FMR geometry [13] (for which TMS processes are suppressed) or sufficiently broadband measurements [14] to extract the bare Gilbert α. For instance, recent FMR linewidth studies on Heusler compounds have reported distinct TMS linewidths [15,16], which challenged simple inference of the Gilbert α.…”
Section: Introductionmentioning
confidence: 99%
“…The TMS effect is usually manifested as FMR fields changing or linewidth broadening [84,86] and widely exists in various ferromagnets. [85][86][87]90] Xue et al confirmed the voltage tuning of TMS in Ni 0.5 Zn 0.5 Fe 2 O 4 (NZFO)/ PMN-PT(011) multiferroic heterostructures fabricated by PLD. [91] Owing to the in-plane anisotropy of the PMN-PT(011) slabs, the voltage modification of the TMS was divided into two modes as the magnetic field was parallel to the (100) or (0 11) plane of the PMN-PT substrates, respectively.…”
Section: Two-magnon Scattering Related Spin Wavesmentioning
confidence: 95%
“…where α int is the Gilbert damping constant, γ is the gyromagnetic ratio, f is the microwave frequency, and ΔH 0 is the inhomogeneous linewidth. One can see from equation ( 4) that ΔH int is linear to f. However, ΔH TMS is not linear to f [20][21][22][23][24][25].…”
Section: Fmr Of γ′-Fe 4 N Films With Different Thicknessesmentioning
confidence: 99%
“…TMS linewidth is induced by the defects and impurities on the surface and interface of ferromagnets. The TMS process plays a very important role in ferromagnetic relaxation, which sometimes can even be dominant [20][21][22][23][24][25]. In this work, epitaxial γ′-Fe 4 N films with a film thickness ranging from 8.5-170.0 nm were deposited on MgO, SrTiO 3 , and LaAlO 3 substrates.…”
Section: Introductionmentioning
confidence: 99%